Wide Hybridization in the Genus Oryza: Aspects and Prospects - ZELIANG, PATU KHATE; PATTANAYAK, ARUNAVA (Indian Journal of Hill Farming, 2014)
The cultivated species of rice has lost many valuable traits for stress tolerance in the process of domestication and selection, which resulted in uniformity in many agronomic traits. Although there are several instances of transfer of useful tolerant genes from the wild rice to the cultivated rice, it has now become essential to look at the newer breeding and selection methods that can be applied to wide hybridization in rice. The paper, discusses issues related to hybridization between different species of the genus Oryza, problems and difficulties encountered and the strategies for a successful breeding program.